KONSERVASI SUMBER MATA AIR BERBASIS KEARIFAN LOKAL DI DESA MEURANDEH KOTA LANGSA ACEH - Habibi, Sultan; Ardian, Syahrul; Asrita, Emelia; Yuni, Rika Ayuwah; Viansa, Audrey; Putri, Nisa Arzikni; Febriansyah, Ahmad Farhan; Natasya, Mutiara; Zahr, Siti Fatimah; Rahayu, Sri; Syafieh, Syafieh (EJOIN : Jurnal Pengabdian Masyarakat, 2024)
Clean water is a primary need for human life, including the people of Meurandeh Village, Langsa City. This research aims to assess the vital role of local wisdom-based spring conservation in clean water accessibility and efforts to accelerate stunting prevention in the local area. By using interview and observation techniques and using the stake model descriptive data analysis technique, it can be concluded that the springs on land owned by PTP-N are used by the people of Meurandeh Village and its surroundings as a source of clean water for their daily needs. These springs can intervene with clean water and sanitation playing a 70% role in preventing stunting. The legacy of local wisdom in spring conservation in Meurandeh Village plays a role in maintaining the availability of clean water in Meurandeh Village and surrounding villages. Thus, this water source is urgently needed to increase accessibility of clean water and proper sanitation to reduce the prevalence of stunting in Meurandeh Village.